Sensitivity Test Of Ethanol Extract Of Senggani Leaves (Melastoma Candidum) On The Growth Shigella Atcc 25931 In Vitro - Rosmaidar, Rosmaidar; Admi, Masda; Riady, Ginta; Isa, M.; Hamzah, Abdullah; Sabri, Mustafa; Nurzalika, Siti (Jurnal Medika Veterinaria, 2023)
Senggani leaves are herbal plants that have antibacterial properties and contain phytochemical compounds in the form of flavonoids, saponins, tannins, steroids, and glycosides. The purpose of this study was to determine the sensitivity of Senggani (Melastoma candidum) leaf extract to the inhibition of the growth of Shigella ATCC 25931 in vitro. Reidentification of bacteria was carried out by Gram staining, and the sensitivity test was conducted on Mueller Hinton Agar media (MHA). Chloramphenicol was used as a positive control, and 1% CMC was used as a negative control. The results of the Gram staining showed Shigella ATCC 25931 bacteria, and the inhibition zone formed at each concentration was 25% (8.26 0.096 mm), 50% (9.02 0.158 mm), and 75% (9.83 0.100 mm). It can be concluded that all concentrations of the ethanol extract of senggani leaves have inhibitory sensitivity to the growth of Shigella ATCC 25931 in the weak category because the inhibition zone formed was 12 mm."